Pendampingan Literasi Menulis Berbasis Proyek di SD Penggerak - Saidillah, Raodah; Subhan, Ali; Kamalia, Hikmah Lailatul; Irfanudin, M Sidik (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2023)
This Community Service aims to create and foster a culture of writing literacy in elementary school students. The method applied is a mentoring method with an Asset Based Community Development (ABCD) approach. The writing literacy assistance in this program focuses on two projects: wall magazines and student bulletins. Participants in this assistance and service were teachers and students at the Penggerak Elementary School (SD), Rejoagung Trangkil. The program of community assistance is divided into four activities which involves Training of Trainers (ToT), Writing Literacy Action Plan (RALMe), School Publication Plan (RPS), and Project Based Literacy Assistance in schools (PLBP). The results obtained were the realization of a project-based writing literacy program and the publication of wall magazines and bulletins at SD 01 Rejoagung.